Target Capture Reveals the Complex Origin of Vietnamese Ginseng - Le, Hien Thi Thu; Nguyen, Linh Nhat; Pham, Hang Le Bich; Le, Hao Thi My; Luong, Toan Duc; Huynh, Hue Thi Thu; Nguyen, Van Tuong; Nong, Hai Van; Teixidor-Toneu, Irene; De Boer, Hugo J.; Manzanilla, Vincent (Frontiers in Plant Science, 2022)
The global market of the medicinal plant ginseng is worth billions of dollars. Many ginseng species are threatened in the wild and effective sustainable development initiatives are necessary to preserve biodiversity at species and genetic level whilst meeting the demand for medicinal produce. This is the case of Panax vietnamensis Ha & Grushv., an endemic and threatened ginseng species in Vietnam that has been the object of national breeding programmes as well as cultivated in various ways by the local population. We capture 353 nuclear makers using the Angiosperm353 probe set. Genetic diversity and population structure of Vietnamese ginseng was evaluated across its area of distribution and from wild and a varying range of cultivated areas. In total, 319 individuals were sampled. After filtering, 1181 SNPs were recovered. From the population statistics, we observe high genetic diversity and high genetic flow between populations. This is also supported by the STRUCTURE analysis. The intense gene flow between populations and very low genetic differentiation is observed regardless of the populations wild or cultivated statues. High levels of admixture from two ancestral populations exist in both wild and cultivated samples. The high gene flow between populations can be attributed to ancient and on-going practices of cultivation, which exist in a continuum from understorey, untended breeding to irrigated farm cultivation and to trade and exchange activities. These results highlight the importance of partnering with indigenous peoples and local communities and taking their knowledge into account for biodiversity conservation and sustainable development of plants of high cultural value.